Effectiveness Method Jogsaw Learning to Increas Students Learning Motivation - Solihah, Siti Maratus; Mu’awanah; Suminta, Rini Risnawita; Chasanah, Umroatun; Rasyid, Fathor (Proceeding International Conference on Education, 2023)
Study This aim For explore application Method Jigsaw Learning in increasing students' learning motivation in Fiqh subjects, especially zakat fitrah material, in class V MI Al Fatah Gerit, Jogorogo District, Ngawi Regency. The research also wants to know what the Jigsaw Learning Method is capable effective increase motivation participant educate in context the. Research purposes: Jigsaw Learning Method Planning : Describes in detail the planning for implementing the Jigsaw Learning Method in increasing learning motivation in Fiqh subjects at MI Al Fatah Gerit. Implementation of the Jigsaw Learning Method : Explains the process of implementing the Method Jigsaw Learning And How method the applied effectively increasing students' learning motivation in Fiqh subjects in class V MI Al Fatah Gerit. Evaluation of the Jigsaw Learning Method: Describes the results of the evaluation of the application of the Jigsaw Learning Method, including its impact on enhancement motivation Study participant educate on material zakat fitrah at MI Al Fatah Gerit. The research results show that the jigsaw learning method can improve motivation Study student so that results Study student increase. This matter can is known from enhancement Which happen from every the meeting in each cycle. It can be seen that the average class score has increased, namely 61.25 in the pre-cycle to 75.63 in the first cycle then to 80.00 in the second cycle. So based on the improvement that occurs in each cycle until it reaches/exceeds the criteria for research completeness, this research is said to be successful/complete.